Customer Satisfaction towards E-Banking Service offered by Prabhu Bank Limited - Timilsina, Pradip (Contemporary Research: An Interdisciplinary Academic Journal, 2023)
In recent times, the internet has become very important in human life. Due to the hastily growing technology in the global market, banking sector has provided the e-banking services to minimize their cost, and digitization strategies in today’s competitive market. This study aims to analyze the association between e-banking service quality and customer satisfaction; and measuring the impact of e-banking service quality on customer satisfaction. The sample size of the study was 100 customers of Prabhu bank operating in Kailali district. Data was collected using a structured five point Likert scale questionnaire conveniently surveyed the customers of Prabhu Bank Limited from study area. Pearson’s correlation and regression analysis was used to analyze the data with the help of statistical package for social science (SPSS-29). The findings of the study concluded that, there is statistically significant positive association between e-banking service quality and customer satisfaction. Furthermore, all the e-banking service quality factors i.e., perceived cost, security and privacy, perceived ease of use, computer self-efficiency and responsiveness has significant positive impact on customer satisfaction. Out of these e-banking service quality factors, perceived ease of use (PEU) has highest impact on customer satisfaction (CS). The findings of this study will help the bank management in improving the e-banking service quality focusing on development of easy and understandable e-banking service for increase their customer’s satisfaction. This study covered only e-banking service quality, future researchers can conduct their study concentrating on overall banking service quality and its impact on customer satisfaction and loyalty.